Adult-onset erythrokeratodermia variabilis (EKV) triggered by pregnancy and crash dieting: A rare case report - Afzal, Ghazal; Najia Ahmed; Nighat Jamal; Fatima Zahoor (Journal of the Pakistan Medical Association, 2024)
Erythrokeratodermia variabilis (EKV) is a rare inherited genodermatosis characterised by migratory and erythematous patches changing over the course of hours to days and fixed keratotic plaques. The disease begins mostly at birth or within the first year of life; it very rarely starts after childhood. We present here a sporadic case with adult onset EKV that was aggravated by pregnancy with spontaneous resolution, and later on, after crash diet more persistent patches and plaques appeared with no spontaneous resolution. The patient showed excellent response to systemic retinoids. Keywords: Acitretin, Adult onset, Crash diet, Erythrokeratodermia variabilis, pregnancy, Retinoids, Sporadic.